Evaluating a Web‐based Point‐of‐care Ultrasound Curriculum for the Diagnosis of Intussusception. Issue 3 (23rd September 2020) - Lin‐Martore, Margaret; Olvera, Michael P.; Kornblith, Aaron E.; Zapala, Matthew; Addo, Newton; Lin, Michelle; Werner, Heidi C.
Abstract: Objectives: Intussusception is a pediatric medical emergency that can be difficult to diagnose. Radiology‐performed ultrasound is the diagnostic study of choice but may lead to delays due to lack of availability. Point‐of‐care ultrasound for intussusception (POCUS‐I) studies have shown excellent accuracy and reduced lengths of stay, but there are limited POCUS‐I training materials for pediatric emergency medicine (PEM) providers. Methods: We performed a prospective cohort study assessing PEM physicians undergoing a primarily Web‐based POCUS‐I curriculum. We developed the POCUS‐I curriculum using Kern's six‐step model. The curriculum included a Web‐based module and a brief, hands‐on practice that was developed with a board‐certified pediatric radiologist. POCUS‐I technical skill, knowledge, and confidence were determined by a direct observation checklist, multiple‐choice test, and a self‐reported Likert‐scale survey, respectively. We assessed participants immediately pre‐ and postcourse as well as 3 months later to assess for retention of skill, knowledge, and confidence. Results: A total of 17 of 17 eligible PEM physicians at a single institution participated in the study. For the direct observation skills test, participants scored well after the course with a median (interquartile range [IQR]) score of 20 of 22 (20–21) and maintained high scores even after 3 months (20 [20–21]). On the written knowledge test, there was significant improvement from 57.4% (95% CI = 49.8 to 65.2) to 75.3% (95% CI = 68.1 to 81.6; p < 0.001) and this improvement was maintained at 3 months at 81.2% (95% CI = 74.5 to 86.8). Physicians also demonstrated improved confidence with POCUS‐I after exposure to the curriculum, with 5.9% reporting somewhat or very confident prior to the course to 76.5% both after the course and after 3 months (p < 0.001). Conclusion: After a primarily Web‐based curriculum for POCUS‐I, PEM physicians performed well in technical skill in POCUS‐I and showed improvement in knowledge and confidence, all of which were maintained over 3 months.